How to prove \begin{align} F_{\mu\rho} \tilde{F}_{\nu}^{\phantom{\nu}\rho} = \frac{1}{4} \eta_{\mu\nu} F_{\rho\sigma} \tilde{F}^{\rho \sigma} \end{align} using Schouten identity \begin{align} 0 = 5 \delta_{\mu}^{[\nu } \epsilon^{\rho\sigma\tau\lambda]} = \delta_{\mu}^{\phantom{\mu}\nu} \epsilon^{\rho\sigma\tau\lambda} +\delta_{\mu}^{\phantom{\mu}\rho}\epsilon^{\sigma\tau\lambda\nu} +\delta_{\mu}^{\phantom{\mu}\sigma}\epsilon^{\tau\lambda\nu\rho} +\delta_{\mu}^{\phantom{\mu}\tau}\epsilon^{\lambda\nu\rho\sigma} +\delta_{\mu}^{\phantom{\mu}\lambda} \epsilon^{\nu\rho\sigma\tau} \end{align} Where the dual tensor is defined in this way \begin{align} \tilde{F}^{\mu\nu} = -\frac{1}{2} i \epsilon^{\mu\nu\alpha\beta} F_{\alpha\beta} \end{align}

My guess \begin{align} &R.H.S=\frac{1}{4} \eta_{\mu\nu} F_{\rho\sigma} \tilde{F}^{\rho \sigma} = -\frac{1}{8} i \eta_{\mu\nu} \epsilon^{\rho\sigma\alpha\beta} F_{\rho\sigma} F_{\alpha\beta} \\ &L.H.S=F_{\mu\rho} \tilde{F}_{\nu}^{\phantom{\nu}\rho} = F_{\mu\rho} \tilde{F}^{x\rho}\eta_{x \nu} = -\frac{1}{2} i \epsilon^{x \rho \alpha \beta} \eta_{x \nu} F_{\mu \rho} F_{\alpha\beta} \\ & \eta_{\mu\nu} \epsilon^{\rho\sigma\alpha\beta} F_{\rho\sigma} F_{\alpha\beta} = 4\epsilon^{x \rho \alpha \beta} \eta_{x \nu} F_{\mu \rho} F_{\alpha\beta} \quad (?) \end{align} To prove the last line i think Schouten identity is needed.

Due to below answer (@Noiralef) Explicit computations are following

Rewrite the schouten identity by pulling down $\nu$ \begin{align} 0 = \eta_{\mu\nu} \epsilon^{\rho\sigma\tau\lambda} +\delta_{\mu}^{\phantom{\mu}\rho}\eta_{x\nu}\epsilon^{\sigma\tau\lambda x} +\delta_{\mu}^{\phantom{\mu}\sigma}\eta_{x\nu}\epsilon^{\tau\lambda x\rho} +\delta_{\mu}^{\phantom{\mu}\tau}\eta_{x\nu}\epsilon^{\lambda x\rho\sigma} +\delta_{\mu}^{\phantom{\mu}\lambda}\eta_{x\nu} \epsilon^{x \rho\sigma\tau} \end{align} Then \begin{align} &\left( \eta_{\mu\nu} \epsilon^{\rho\sigma\tau\lambda} +\delta_{\mu}^{\phantom{\mu}\rho}\eta_{x\nu}\epsilon^{\sigma\tau\lambda x} +\delta_{\mu}^{\phantom{\mu}\sigma}\eta_{x\nu}\epsilon^{\tau\lambda x\rho} +\delta_{\mu}^{\phantom{\mu}\tau}\eta_{x\nu}\epsilon^{\lambda x\rho\sigma} +\delta_{\mu}^{\phantom{\mu}\lambda}\eta_{x\nu} \epsilon^{x \rho\sigma\tau} \right) F_{\rho\sigma}F_{\tau\lambda} \\ &=\eta_{\mu\nu} \epsilon^{\rho\sigma\tau\lambda}F_{\rho\sigma}F_{\tau\lambda} + \epsilon^{\sigma\tau\lambda x} \eta_{x\nu} F_{\mu\sigma}F_{\tau\lambda} + \epsilon^{\tau\lambda x\rho} \eta_{x\nu} F_{\rho\mu}F_{\tau\lambda} + \epsilon^{\lambda x \rho\sigma}\eta_{x\nu} F_{\rho\sigma}F_{\mu\lambda}+ \epsilon^{x \rho\sigma\tau} \eta_{x\nu}F_{\rho\sigma} F_{\tau\mu} \\ & = \eta_{\mu\nu} \epsilon^{\rho\sigma\tau\lambda}F_{\rho\sigma}F_{\tau\lambda} + 4\epsilon^{\sigma\tau\lambda x} \eta_{x\nu} F_{\mu\sigma}F_{\tau\lambda} =0 \\ & \quad \Rightarrow \quad \eta_{\mu\nu} \epsilon^{\rho\sigma\tau\lambda}F_{\rho\sigma}F_{\tau\lambda} =- 4\epsilon^{\sigma\tau\lambda x} \eta_{x\nu} F_{\mu\sigma}F_{\tau\lambda} = 4\epsilon^{x \sigma\tau\lambda } \eta_{x\nu} F_{\mu\sigma}F_{\tau\lambda} \end{align} Here we used \begin{align} \epsilon^{\tau\lambda x \rho} F_{\rho\mu} F_{\tau\lambda} = \epsilon^{\tau\lambda x \sigma} F_{\sigma\mu} F_{\tau\lambda} = (-1)^3 \epsilon^{\sigma\tau\lambda x} F_{\sigma\mu} F_{\tau\lambda} = \epsilon^{\sigma\tau\lambda x} F_{\mu\sigma} F_{\tau\lambda} \end{align}


closed as off-topic by JamalS, ACuriousMind, Danu, Kyle Kanos, Martin May 4 '15 at 13:45

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "Homework-like questions should ask about a specific physics concept and show some effort to work through the problem. We want our questions to be useful to the broader community, and to future users. See our meta site for more guidance on how to edit your question to make it better" – JamalS, ACuriousMind, Danu, Kyle Kanos
If this question can be reworded to fit the rules in the help center, please edit the question.


Rewrite the Shouten identity by pulling down $\nu$: $$ 0 = \eta_{\mu\nu} \epsilon^{\rho\sigma\tau\lambda} + \delta_\mu^\rho \eta_{\chi\nu} \epsilon^{\sigma\tau\lambda\chi} + \cdots$$ Then plug this into the left hand side of the equation you marked with (?). You will get four terms, all having the correct structure of the right hand side (one free index at $\eta$ and one at one of the $F$'s, all other lower indices are contracted with the $\epsilon$).

Now you only have to check that everything works out and those terms have the same signs, so you arrive at the right hand side.


Not the answer you're looking for? Browse other questions tagged or ask your own question.